A TRANSDISCIPLINARY MODEL OF ENTREPRENEURIAL COMPETENCE AND CAREER DEVELOPMENT - Nur Fadhilah Umar; Nurhikmah Nurhikmah; Abdul Hakim (JURNAL NALAR PENDIDIKAN, 2025)
This study aims to develop a transdisciplinary model of entrepreneurial competence and career development based on bibliometric analysis and the integration of cross-disciplinary theories. The research is grounded in the demands of the digital economy era, which requires entrepreneurial competence that is not only technical in nature, but also encompasses career readiness, psychological resilience, and digital competence. A mixed-method approach was employed, combining bibliometric analysis and conceptual study. Data were obtained from international journal databases (2018–2025) and analyzed using VOSviewer to produce network visualizations, overlay visualizations, and density maps. Of the 2,087 identified publications, 253 articles met the inclusion criteria and were analyzed further. The results reveal several main clusters, including entrepreneurial education, entrepreneurial competence, attitude, digital competence, growth mindset, resilience, and career readiness, all of which are interrelated. Another important finding is the role of digital competence as a bridge between entrepreneurship education, core competence, and career readiness. This study produces a transdisciplinary model that integrates educational, psychological, technological, social, and career dimensions, and provides implications for the development of more adaptive entrepreneurship education curricula and policies in the digital era